2022
DOI: 10.3390/jcm11237068
|View full text |Cite
|
Sign up to set email alerts
|

A Machine-Learning Model for the Prognostic Role of C-Reactive Protein in Myocarditis

Abstract: Aims: The role of inflammation markers in myocarditis is unclear. We assessed the diagnostic and prognostic correlates of C-reactive protein (CRP) at diagnosis in patients with myocarditis. Methods and results: We retrospectively enrolled patients with clinically suspected (CS) or biopsy-proven (BP) myocarditis, with available CRP at diagnosis. Clinical, laboratory and imaging data were collected at diagnosis and at follow-up visits. To evaluate predictors of death/heart transplant (Htx), a machine-learning ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…To date, no definitive evidence of biopsy-proven myocarditis caused by SARS-CoV-2 infection or vaccination has been found. Conversely, a study demonstrated that SARS-CoV-2 vaccination is safe for patients with prior myocarditis; additionally, this study showed an absence of increased risk of myocarditis relapse after SARS-CoV-2 infection in the same patients' population [21].…”
Section: Etiology: Infectious Versus Non-infectious Myocarditismentioning
confidence: 57%
See 1 more Smart Citation
“…To date, no definitive evidence of biopsy-proven myocarditis caused by SARS-CoV-2 infection or vaccination has been found. Conversely, a study demonstrated that SARS-CoV-2 vaccination is safe for patients with prior myocarditis; additionally, this study showed an absence of increased risk of myocarditis relapse after SARS-CoV-2 infection in the same patients' population [21].…”
Section: Etiology: Infectious Versus Non-infectious Myocarditismentioning
confidence: 57%
“…Presence of circulating heart-specific autoantibodies in patients with inflammatory cardiomyopathy and their relatives. Caforio et al, 2007 [24] Mestroni et al, 1999 [25] Baritussio et al, 2022 [26] Animal models of experimentally induced inflammatory cardiomyopathy, with or without a DCM phenotype, after immunization with specific auto-antigen(s). Li et al, 2006 [27] Response to immunosuppressive or immunomodulant therapy in patients with virus-negative inflammatory cardiomyopathy.…”
Section: Kindermann Et Al 2008 [23]mentioning
confidence: 99%
“…A normal hsCRP is rare even 2 days after the event, whereas Loeffler endocarditis has also shown elevated CRP levels [244,245]. CRP has been noted for its prognostic role in lymphocytic, eosinophilic, autoimmune, and viral myocarditis [246,247].…”
Section: Cardiological Disordersmentioning
confidence: 99%
“…Endocarditis, myocarditis, and pericarditis resulting from various etiologies were previously discussed [3,[240][241][242][243][244][245][246][247]. A CRP of more than 720 mg/L can predict high-risk individuals with a high in-hospital mortality rate due to infective endocarditis [893].…”
Section: C-reactive Protein and Infectionsmentioning
confidence: 99%